Hydrogen Physisorption Energies for Bumpy, Saturated, Nitrogen-Doped Single-Walled Carbon Nanotubes - Rozas-Soto, R; Contreras-Fuentes, M (Springer New York LLC, 2016)
Finite saturated regular carbon nanotubes (CNTs) are predicted to exhibit higher capacity as hydrogen storage media compared to unsaturated regular CNTs. In the present study, molecular hydrogen physisorption energies (MHPEs) for finite saturated and unsaturated bumpy defected CNTs were calculated by density functional theory (DFT-D3) methods at the B3LYP/6-31G(d) theory level, with rigorous inclusion of van der Waals interactions. The calculated MHPEs for both regular and bumpy defected armchair, chiral and zigzag CNTs with similar diameters and lengths, with and without nitrogen doping, were compared in terms of Eph/H2, defined as the MHPE per hydrogen molecule adsorbed inside the nanotube. For all studied systems, Eph/H2 increased with the number of physisorbed hydrogen molecules. Nitrogen doping of regular and bumpy CNTs resulted in an increase in the Eph/H2 values, with the exception of bumpy chiral nanotubes. The results of this study demonstrate that bumpy defects are important nanotube structural features whose effects depend on nanotube chirality. For instance, bumpy defects were beneficial for undoped and doped zigzag nanotubes, resulting in a decrease in Eph/H2 values for regular structures from 0.5 and 0.74 to 0.26 and 0.42 eV, respectively. By contrast, for doped armchair regular structures with an Eph/H2 value of 0.38 eV, bumpy defects increased Eph/H2 to 0.45 eV. These Eph/H2 values for bumpy doped armchair and the zigzag nanotubes are all within the range of 0.1–0.5 eV/H2 reported as ideal for reversible hydrogen storage under environmental conditions. © 2016, Springer Science+Business Media New York.